2x+3x-9=x+3

Simple and best practice solution for 2x+3x-9=x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3x-9=x+3 equation:


Simplifying
2x + 3x + -9 = x + 3

Reorder the terms:
-9 + 2x + 3x = x + 3

Combine like terms: 2x + 3x = 5x
-9 + 5x = x + 3

Reorder the terms:
-9 + 5x = 3 + x

Solving
-9 + 5x = 3 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-9 + 5x + -1x = 3 + x + -1x

Combine like terms: 5x + -1x = 4x
-9 + 4x = 3 + x + -1x

Combine like terms: x + -1x = 0
-9 + 4x = 3 + 0
-9 + 4x = 3

Add '9' to each side of the equation.
-9 + 9 + 4x = 3 + 9

Combine like terms: -9 + 9 = 0
0 + 4x = 3 + 9
4x = 3 + 9

Combine like terms: 3 + 9 = 12
4x = 12

Divide each side by '4'.
x = 3

Simplifying
x = 3

See similar equations:

| 6-2[3(x+3)-5]= | | 7(x+1)-7=4x+3(1+x) | | 17+x=34 | | 16=25-x | | X+56=5x+24 | | 5u^2+9u+4=0 | | 7x-14=3x-6 | | 10=5r-3r | | 11x-(7x-4)= | | 4(1-4n)-5n=19-6n | | 3(2n-2)=(9n+2)+7 | | -(4xy-9)+2(6xy+8)= | | 10x+3=4(2x+1)-x+6 | | 10-9x=9x+20 | | -2+9=y-2 | | (4r+3)(r-8)=-(5r-40) | | 5(z-4)+5z-2= | | 5t+4t=45-16+7 | | -6(x+4)+6(2x+1)= | | (x+8)(x-5)=-30 | | -3r-8=-6r+4r | | -1+6-5=-5a+6a | | -50=-10z | | x^2+48x+576=100x | | y=fx+n | | 6y-2(y-3)+6= | | 5-4(b-4)=17-2b | | -2y-3.5=15.2 | | -3(7+-13)= | | b=2a | | 9(1.07)-3y=6 | | -(3y-5)+10= |

Equations solver categories